A cross-cultural examination of racial identity and racial preference of preschool children in the West Indies - Gopaul-McNicol, Sharon-Ann
This study investigated the racial attitudes of 302 preschool children in the Caribbean whose racial preference was tested using black and white Cabbage Patch dolls. Standard Clark doll questions, plus four researcher-supplied questions, were individually administered. Findings show that 71.9 percent of the children chose to play with a white doll, indicating the debilitating effect of colonialism on West Indians
doi: 10.1177/0022022195262002
Keywords: Preschool children